Unanticipated Political Events and Their Effect on the Nepalese Insurance Sector and Stock Market - Karki, Dipendra; Kakshyapati, Sajan; Bhattarai, Ganesh; Fakhfakh, Hamadi; Randika, Dilini (Nepalese Journal of Insurance and Social Security, 2024)
This study analyzes the relationship between unanticipated political events and their profound impact on both the insurance sector and the Nepalese stock market (NEPSE). Utilizing comprehensive analysis, the research spans 200 days before to 10 days after the political event’s announcement. Employing Levene’s test, dummy variable regression, and estimated average abnormal return, the study reveals significant effects of political events on the insurance index and NEPSE indices. The pre-event period is particularly significant, indicating potential information leakage. Window Frame 1 (-10, -1) stands out as the most profoundly impacted period, with Window Frame 2 (0, +10) witnessing moderate impact during the announcement and Window Frame 3 (+2, +10) experiencing a comparatively lesser post-event effect. Nepali Congress Wins Election (Event 1) and End of Nepal Blockade (Event 3) were identified as the most significant events for the Insurance and NEPSE indexes. Dummy variable regression emphasizes the significance (P < 0.05) of multiple window frames (mostly 1, 5, & 6) in the NEPSE index, suggesting early information leakage adjustments. The insurance sector also demonstrates a highly significant (P < 0.05) impact of unanticipated political events across various data points, with the post-event period (Windows 2 and 3) as the sole exception. Cumulative abnormal return analysis demonstrates that the Nepalese stock market is moderately inefficient, as it reinforces the market’s attempt to incorporate political influences within three to five days of the announcement date. These findings bear implications for investors, policymakers, and regulatory authorities seeking to understand the dynamics of the Nepalese stock market, enabling informed decision-making during times of political transitions and uncertainty.